Effect of Ketamine on Human Neurochemistry in Posterior Cingulate Cortex: A Pilot Magnetic Resonance Spectroscopy Study at 3 Tesla - Bednarik, Petr; Spurny, Benjamin; Silberbauer, Leo R.; Svatkova, Alena; Handschuh, Patricia A.; Reiter, Birgit; Konadu, Melisande E.; Stimpfl, Thomas; Spies, Marie; Bogner, Wolfgang; Lanzenberger, Rupert (Frontiers in Neuroscience, 2021)
Ketamine is a powerful glutamatergic long-lasting antidepressant, efficient in intractable major depression. Whereas ketamine’s immediate psychomimetic side-effects were linked to glutamate changes, proton MRS (1H-MRS) showed an association between the ratio of glutamate and glutamine and delayed antidepressant effect emerging ~2 hours after ketamine administration. While most 1H-MRS studies focused on anterior cingulate, recent functional MRI connectivity studies revealed an association between ketamine’s antidepressant effect and disturbed connectivity patterns to the posterior cingulate cortex (PCC), and related PCC dysfunction to rumination and memory impairment involved in depressive pathophysiology. The current study utilized the state-of-the-art single-voxel 3T sLASER 1H-MRS methodology optimized for reproducible measurements. Ketamine’s effects on neurochemicals were assessed before and ~3 hours after intravenous ketamine challenge in PCC. Concentrations of 11 neurochemicals, including glutamate (CRLB ~ 4%) and glutamine (CRLB ~ 13%), were reliably quantified with the LCModel in 12 healthy young men with between-session coefficients of variation (SD/mean) <8%. Also, ratios of glutamate/glutamine and glutamate/aspartate were assessed as markers of synaptic function and activated glucose metabolism, respectively. Pairwise comparison of metabolite profiles at baseline and 193±4 minutes after ketamine challenge yielded no differences. Minimal detectable concentration differences estimated with posthoc power analysis (power = 80%, alpha = 0.05) were below 0.5 mol/g, namely 0.39 mol/g (~4%) for glutamate, 0.28 mol/g (~10%) for Gln, ~14% for glutamate/glutamine and ~8% for glutamate/aspartate. Despite the high sensitivity to detect between-session differences in glutamate and glutamine concentrations, our study did not detect delayed glutamatergic responses to subanesthetic ketamine dose in PCC.